2008
DOI: 10.2106/jbjs.g.00806
|View full text |Cite
|
Sign up to set email alerts
|

Autograft Contamination During Preparation for Anterior Cruciate Ligament Reconstruction

Abstract: A high rate (12%) of autograft contamination can be expected during autograft preparation for anterior cruciate ligament reconstruction. The contamination rate is almost equal for both bone-patellar tendon-bone and hamstring tendon autografts. We could not identify an association between contaminated grafts implanted in the knee and postoperative inflammatory markers such as the erythrocyte sedimentation rate and the C-reactive protein level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
65
1
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 21 publications
11
65
1
7
Order By: Relevance
“…2,4,15,16,23,27,29 In the majority of our patients, an identical technique was used; thus, we can present reliable results for this standardized technique, but we cannot evaluate differences with regard to the graft choice or fixation method. With regard to graft contamination, Hantes et al 13 showed a colonization rate of 10% to 13% of the grafts during preparation. Although there was no postoperative infection, this might be a factor in the development of intra-articular infections.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,15,16,23,27,29 In the majority of our patients, an identical technique was used; thus, we can present reliable results for this standardized technique, but we cannot evaluate differences with regard to the graft choice or fixation method. With regard to graft contamination, Hantes et al 13 showed a colonization rate of 10% to 13% of the grafts during preparation. Although there was no postoperative infection, this might be a factor in the development of intra-articular infections.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that grafts with intraoperative positive cultures do not necessarily progress to clinical infection 6,[25][26][27] . However, those studies did not examine situations with a known contamination event, which may increase the likelihood of a clinically important infection.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical masks, gloves, and insufficiently sterilized instruments can also be a source of graft contamination [28]. A graft implanted in the knee joint does not have initial vascularization, so antibiotics are not effective [28,29]. Hantes et al [29] proved that seven out of 60 (12%) microbiologically examined grafts were initially contaminated, mostly with Staphylococcus, although a postoperative infection did not develop in any of these cases.…”
Section: Graph 1 Symptoms Of Infection After Acl Reconstruction Grafmentioning
confidence: 99%